Mosquito Fauna (Diptera: Culicidae) of Hamedan County, Western Iran. - Amir Hossein Zahirnia; Hamid Zendehfili (Tehran University of Medical Sciences, 2014)
Background: This study aimed to identify and determine the larval and adult mosquitoes (Culicidae) fauna in Hamedan County, western Iran. Methods: It was a cross-sectional study which took place in four area of the Hamedan County. Sampling methods for larvae, pupae and adults were dipping, hand catch, night catch and total catch. Larvae and adult mosquitoes col- lected and were sent to laboratory of Medical Entomology, Hamedan University of Medical Sciences, Hamedan, Iran for further identification to species level to determination of fauna. Data analysis was performed using SPSS soft- ware version19. Results: Three genera and eight species of family Culicidae were collected and identified in Hamedan County, Hamedan Province, West Iran, during May to October 2013. These species included: Culex theileri, Cx. pipiens, Cx. antennatus, Culiseta subochrea, Cs. langiareolata, Anopheles superpictus, An. maculipennis and An. stephensi. The species Cx. antennatus and An. stephensi were reported for the first time in Hamedan County. Conclusion: An. stephensi and Cx. antennatus caught had not been previously recorded in Hamedan Province. Due to vast agricultural activities in the province which provides suitable environment for the establishment of various species of mosquitoes and since many of them are potential vectors of human and domesticated animal pathogens,their ecology needs to be studied extensively.